2018
DOI: 10.1002/btpr.2650
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of ethyl esters from waste oil using mixtures of lipases in a plug‐flow packed‐bed continuous reactor

Abstract: This work describes the continuous synthesis of ethyl esters via enzymatic catalysis on a packed-bed continuous reactor, using mixtures of immobilized lipases (combi-lipases) of Candida antarctica (CALB), Thermomyces lanuginosus (TLL), and Rhizomucor miehei (RML). The influence of the addition of glass beads to the reactor bed, evaluation of the use of different solvents, and flow rate on reaction conditions was studied. All experiments were conducted using the best combination of lipases according to the fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 46 publications
0
39
0
Order By: Relevance
“…40,41 The biological function of lipases is the hydrolysis of triglycerides to produce free fatty acids and glycerol. 42 The heterogeneity of the natural substrate [43][44][45][46][47][48] has converted lipases in enzymes with a very broad specificity, accepting substrates very different from glycerides (even amides). Thus, lipases are used in vitro to catalyze reactions different from those of the natural hydrolase function, [49][50][51][52][53][54] such as esterification, [55][56][57][58][59][60][61] acidolysis, [62][63][64][65][66][67] interesterificaton, [68][69][70][71] transesterification, [72][73][74][75][76] aminolysis, [77][78][79][80][81] perhydrolysis, 82,83 etc., together with a collection of the so-called promiscuous reactions.…”
Section: Lipases In Biocatalysismentioning
confidence: 99%
“…40,41 The biological function of lipases is the hydrolysis of triglycerides to produce free fatty acids and glycerol. 42 The heterogeneity of the natural substrate [43][44][45][46][47][48] has converted lipases in enzymes with a very broad specificity, accepting substrates very different from glycerides (even amides). Thus, lipases are used in vitro to catalyze reactions different from those of the natural hydrolase function, [49][50][51][52][53][54] such as esterification, [55][56][57][58][59][60][61] acidolysis, [62][63][64][65][66][67] interesterificaton, [68][69][70][71] transesterification, [72][73][74][75][76] aminolysis, [77][78][79][80][81] perhydrolysis, 82,83 etc., together with a collection of the so-called promiscuous reactions.…”
Section: Lipases In Biocatalysismentioning
confidence: 99%
“…This is based on the fact that an oil is a heterofunctional substrate composed of many different glycerides, and very likely some of them may behave even as inhibitors of the best lipase for the main components of the oil. Thus, the use of mixtures of lipases in these reactions is becoming increasingly popular (Alves et al, 2014;Ibrahim et al, 2008;Poppe et al, 2015Poppe et al, , 2018bPoppe et al, , 2018aQiao et al, 2017;Rodrigues and Ayub, 2011).…”
Section: Combilipasesmentioning
confidence: 99%
“…For example, to prepare tailor-made lipase combilipases (as the same support may immobilize many different lipases) or lipase coimmobilized with other enzymes (after modifying the immobilized lipase with polyethylenimine) may have a great interest (Zaak et al, 2017c). Although this has been already reported in some instances(Peirce et al, 2016b; Zaak et al, 2017c), the possibilities are many and a deeper exploration must be carried out, as combilipases have proven to be a potent tool in reactions as interesting as oil hydrolysis or biodiesel production(Alves et al, 2014;Ibrahim et al, 2008;Poppe et al, 2015 Poppe et al, , 2018bPoppe et al, , 2018aQiao et al, 2017;Rodrigues and Ayub, 2011).…”
mentioning
confidence: 91%
“…However, these features become a problem when the biocatalyst is going to be utilized in the full modification of a heterogeneous substrate. This is the case of oils, either when they are hydrolyzed to produce free fatty acids or when they are used in transesterifications to produce biodiesel [16][17][18][19][20][21][22][23]. It should be considered that the oil will be composed of many different triglycerides formed by different fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is not easy to find an "optimal" enzyme that may be the best one in all situations. In these cases, it has been shown that the combined use of several lipases permits not only better yields but also higher initial reaction rates and more lineal reaction courses (in some cases one enzyme eliminates an inhibitor of the main enzyme) [16][17][18][19][20][21][22][23]. Usually, this has been obtained using mixtures of individually immobilized lipases [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%